Ways out of the Dictionary: Hyperlinks to Other Sources in German and African Online Dictionaries - Klosa-Kückelhaus, Annette (Lexikos, 2023)
This study examines a number of German and African online dictionaries to see how they make use of the possibility of linking to external sources (e.g. other dictionaries, encyclopaedias, or even corpus data). The article investigates which hyperlinks occur at which places in the word articles and how these are presented to the dictionary users. This is done against the background of metalexicographic considerations on the planning of outer features and the mediostructure in online dictionaries as well as different categorizations of hyperlinks in online reference works. The results show that retro-digitized dictionaries make virtually no use of hyperlinks to external sources. Genuine online dictionaries, on the other hand, do, but often in a form that needs improvement, since, for example, explanations of dictionary-external links are not always found in the user guide and their design is different even within a dictionary.Keywords: online dictionaries, retro-digitized dictionaries, mediostructure, hyperlinks, African languages, German